Nodeless superconductivity in the cage-type superconductor Sc5Ru6Sn18 with preserved time-reversal symmetry. (16th July 2018) - Kumar, D; Kuo, C N; Astuti, F; Shang, T; Lee, M K; Lue, C S; Watanabe, I; Barker, J A T; Shiroka, T; Chang, L J
Abstract: We report the single-crystal synthesis and detailed investigations of the cage-type superconductor Sc5 Ru6 Sn18, using powder x-ray diffraction (XRD), magnetization, specific-heat and muon-spin relaxation ( µ SR) measurements. Sc5 Ru6 Sn18 crystallizes in a tetragonal structure (space group I 41 / acd ) with lattice parameters a   =  1.387(3) nm and c   =  2.641(5) nm. Both DC and AC magnetization measurements prove the type-II superconductivity in Sc5 Ru6 Sn18 with T c   ≈  3.5(1) K, a lower critical field   =  157(9) Oe and an upper critical field,   =  26(1) kOe. The zero-field electronic specific-heat data are well fitted using a single-gap BCS model, with   =  0.64(1) meV. The Sommerfeld constant γ varies linearly with the applied magnetic field, indicating s -wave superconductivity in Sc5 Ru6 Sn18 . Specific-heat and transverse-field (TF) µ SR measurements reveal that Sc5 Ru6 Sn18 is a superconductor with strong electron–phonon coupling, with TF- µ SR also suggesting a single-gap s -wave character of the superconductivity. Furthermore, zero-field µ SR measurements do not detect spontaneous magnetic fields below T c, hence implying that time-reversal symmetry is preserved in Sc5 Ru6 Sn18 .